A Regularly Channeled Lamellar Membrane for Unparalleled Water and Organics Permeation. Issue 23 (23rd March 2018) - Wang, Jingtao; Chen, Pingping; Shi, Benbing; Guo, Weiwei; Jaroniec, Mietek; Qiao, Shi‐Zhang
Abstract: Lamellar membranes show exceptional molecular permeation properties of key importance for many applications. However, their design and development need the construction of regular and straight interlayer channels and the establishment of corresponding transport rate equation. The fabrication of a uniformly lamellar membrane is reported using double‐layered Ti3 C2 T x MXenes as rigid building blocks. This membrane possesses ordered and straight 2 nm channels formed via a direct self‐stacking, in contrast to the conventional irregular ones from flexible sheets. Such channels permit precise molecular rejection and unparalleled molecular permeation. The permeance of water and organics by this membrane reached 2300 and 5000 L m −2  h −1  bar −1, respectively. The molecular transfer mechanism in confined nanochannels, and the corresponding model equation are established, paving a way to nanoscale design of highly efficient channeled membranes for transport and separation applications. Abstract : A lamellar membrane with regular, straight, and robust 2 nm interlayer channels are fabricated using double‐layered Ti3 C2 T x MXenes as rigid building blocks via a direct self‐stacking. Such channels permit precise molecular rejection, and unparalleled permeation spanning from water to organics, which make them superior in comparison to those formed by flexible GO sheets.